Large Mammary Paget Disease without Underlying Breast Carcinoma - Prakasit Chirappapha, MD; Lakkana Adireklarpwong, MD; Pattana Sornmayura, MD; Panuwat Lertsithichai, MD; Chayanoot Rattadilok, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Mammary Paget disease is an uncommon type of breast cancer. Redness, scaling, and thickness involving the nipple and areola are common clinical symptoms. Invasive breast cancer was found in nearly 90% of these patients. Only a few cases of mammary Paget disease with no underlying cancer have been described, with a better prognosis. Treatment options include wide excision or mastectomy. However, if the lesion is very extensive, breast reconstruction may be required. We reported a rare case of extensive Paget disease in a 65-year-old woman who had a 7-year history of a 14 × 19 cm progressively enlarging erythematous scaling lesion that covered her entire left breast. No evidence of related malignancy or metastatic lesion was seen. A left mastectomy with sentinel lymph node biopsy and immediate pedicled transverse rectus abdominis myocutaneous flap reconstruction was chosen. There is uncertainty about axillary node metastasis since multiple enlarged and palpable left axillary lymph nodes were seen. She had axillary lymph node dissection instead. A histological examination confirmed the diagnosis of Paget disease of the nipple in the absence of underlying breast cancer and there was no evidence of axillary lymph node metastasis. This article emphasizes the need to pay close attention to diagnosis, progression, and treatment of the disease.